2022
DOI: 10.3389/fmolb.2022.935375
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of ABHD5 Structure and Ligand Recognition

Abstract: Alpha/beta hydrolase domain-containing 5 (ABHD5), also termed CGI-58, is the key upstream activator of adipose triglyceride lipase (ATGL), which plays an essential role in lipid metabolism and energy storage. Mutations in ABHD5 disrupt lipolysis and are known to cause the Chanarin-Dorfman syndrome. Despite its importance, the structure of ABHD5 remains unknown. In this work, we combine computational and experimental methods to build a 3D structure of ABHD5. Multiple comparative and machine learning-based homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…Robinson et al utilized the RF algorithm to provide a rapid screening method to quantitatively predict thiolase activity for different nitrophenyl esters, deducing that oxygen content is the most important chemical feature for predicting enzyme activity . In addition, AI software such as Alphafold2 was used to simulate the reliable molecular structure of α/β hydrolase domain 5 (ABHD5), a key activator of lipase, and amino acid residues easily stably bound by different ligand binding modes were found, which also has significance for promoting enzyme activity …”
Section: Improved Performance Of Lipase By Aimentioning
confidence: 99%
See 1 more Smart Citation
“…Robinson et al utilized the RF algorithm to provide a rapid screening method to quantitatively predict thiolase activity for different nitrophenyl esters, deducing that oxygen content is the most important chemical feature for predicting enzyme activity . In addition, AI software such as Alphafold2 was used to simulate the reliable molecular structure of α/β hydrolase domain 5 (ABHD5), a key activator of lipase, and amino acid residues easily stably bound by different ligand binding modes were found, which also has significance for promoting enzyme activity …”
Section: Improved Performance Of Lipase By Aimentioning
confidence: 99%
“…152 In addition, AI software such as Alphafold2 was used to simulate the reliable molecular structure of α/β hydrolase domain 5 (ABHD5), a key activator of lipase, and amino acid residues easily stably bound by different ligand binding modes were found, which also has significance for promoting enzyme activity. 153 Increasing enzyme activity is usually needed in lipase applications. However, in some cases, inhibition of lipase activity is also welcomed (Figure 6A).…”
Section: Application Of Ai Technology For Lipase Activity Improvement...mentioning
confidence: 99%
“…Thus, it was demonstrated that the wild-type hydrogen bond network is crucial for the activity of alpha/beta hydrolase domain-containing 5 (ABHD5), also known as CGI-58, which is the activator of adipose triglyceride lipase (ATGL) [ 39 ]. Indeed, computational modeling showed that mutations to E41, R116, and G328 disrupt the hydrogen bonding network with surrounding residues and inhibit membrane targeting or ATGL activation [ 70 ]. Another study focused on the T cell receptor’s interaction with the peptide major histocompatibility complex and showed that hydrogen bonds and Lennard–Jones contacts, which are physicochemical aspects of the TCR–pMHC dynamic bond strength, are correlated with the immunogenic response brought on by the particular peptide in the MHC groove [ 71 ].…”
Section: Electrostatics Of Wild-type Biological Macromoleculesmentioning
confidence: 99%
“…ABDH5 is a multimeric protein that activates intracellular lipases such as adipose triglyceride lipase (ATGL), which plays a significant role in lipolysis. Simulations using machine learning-based homology modeling methods have suggested that mutations in genes E41, R116, and G328 disturb hydrogen bonding networks and suppress ATGL activation [4]. CDS has also been described as a "neutral lipid storage disease (NLSD) with ichthyosis" owing to the neutral lipids that are deposited in a variety of organs, including the skin, muscle, liver, central nervous system, and granulocytes [5].…”
Section: Introductionmentioning
confidence: 99%